The Effectiveness of Traditional Media (Leaflet and Poster) to Promote Health in a Community Setting in the Digital Era: A Systematic Review - Ardila Lailatul Barik; Rizki Agustin Purwaningtyas; Dwi Astuti (Jurnal Ners, 2019)
Introduction: The use of health promotion media in the digital era, such as e-health and m-health, is increasing. However, traditional health promotion media, such as posters and leaflets, are still used. This review aimed to identify the effectiveness of the use of traditional health promotion media (leaflets and posters) in a community setting in the digital era.Methods: The data was gathered using the following steps: (1) determining the topic, (2) determining the keyword chain, (3) looking for the relevant literature in the database and (4) analyzing the article. The search using a predetermined keyword chain in Scopus, Science Direct and Sage Journals produced 208 publications.Results: After applying the inclusion and exclusion criteria, 16 publications were selected for review.Conclusion: Traditional health promotion media such as leaflets and posters are still useful in the current digital era, especially for adult respondents. This form of media will be more effective when combined with other media such as videos, telephone interactions, games and others.